The effectiveness of using textual glossary and multimedia annotation in L2 vocabulary learning in self-access centre: a case study of diploma students of UiTM Pulau Pinang / Lim Teck Heng and Gopighantan Mylvaganam - Lim, Teck Heng; Mylvaganam, Gopighantan (2008)
This study attempts to examine the effectiveness of the use of electronic glossary namely Textual Glossary and Multimedia Annotation in L2 vocabulary learning among a group of diploma learners of English at UiTMPP. Textual Glossary is a glossary that provides definition and/or meanings of a lexical item in the form of text only. Multimedia Annotation, on the other hand, is a glossary that provides definition and/or meanings of a lexical item with the use of text and pictures. The subjects in the study were divided into two groups. Each group received two treatments. In one treatment, the subjects were required to read a passage that was glossed with Textual Glossary. In the other treatment, the same subjects read another passage glossed with Multimedia Annotation. The results obtained showed that both Textual Glossary and Multimedia Annotation are effective in helping the students to acquire and recall the target lexical items. There is, however, no significant difference between the two modes in terms of their effectiveness. The conclusion made was the preference to the type of glossing depends largely on the learning style of the students.